PENGARUH KECEPATAN ALIRAN UDARA DENGAN PENGATURAN DIMMER PADA TEKANAN UDARA MASUK PADA PROSES GASIFIKASI SEKAM PADI TERHADAP PEMBENTUKAN FLAMABLE GAS - Suliono Suliono; Felix Dionisius; Bambang Sudarmanta (Jurnal Teknologi Terapan, 2020)
The biomass gasification process is a way to obtain combustible syn-gas through combustion of biomass in a closed reactor with the help of air from a compressed blower. Without the help of air gas formation process is not possible, the combustion in the furnace must have air that can start a fire. The tool for supplying air is a pressure blower. The purpose of this study was to obtain a stoichiometric air and biomass mixture in the rice husk gasification process. With the stoichiometric air fuel ratio (AFR) in the rice husk gasification process, it will produce a perfect flammable syn-gas.The method used in this research is to change the rice husk solid through the gasification process. The gas released in the gasification process will be varied at the blower speed with or without using a dimmer. From the test results, it can be seen in the syn-gas output from the reactor. on dimmer 1 the inlet airspeed is 3.5 m / s, on dimmer 2 the airspeed is 4.0 m / s. In dimmer 3 the air velocity is 4.5 m / s and in dimmer 4 the air velocity produced is 5.0 m / s From the results of testing the air velocity of each variation that enters the reactor only air velocity 4.5 m / s and 5.0 m / s or in dimmers 3 and 4 which can produce flammable syn-gas.